Fully covered self-expandable metal stent in the treatment of postsurgical colorectal diseases: outcome in 29 patients. (March 2016) - Cereatti, Fabrizio; Fiocca, Fausto; Dumont, Jean-Loup; Ceci, Vincenzo; Vergeau, Bertrand-Marie; Tuszynski, Thierry; Meduri, Bruno; Donatelli, Gianfranco
Background: Self-expandable metal stent (SEMS) placement is a minimally invasive treatment for palliation of malignant colorectal strictures and as a bridge to surgery. However, the use of SEMS for benign colorectal diseases is controversial. The purpose of this retrospective study is to evaluate the efficacy and safety of fully covered SEMS (FCSEMS) placement in postsurgical colorectal diseases. Methods: From 2008 to 2014, 29 patients with 32 FCSEMS deployment procedures were evaluated. The indications for stent placement were: 17 anastomotic strictures (3/17 presented complete closure of the anastomosis); four anastomotic leaks; seven strictures associated with anastomotic leak; and one rectum-vagina fistula. Results: Clinical success was achieved in 18 out of 29 patients (62.1%) being symptom-free at an average of 19 months. In the remaining 11 patients (37.9%), a different treatment was needed: four patients required multiple endoscopic dilations, 4 patients colostomy confection, one patient definitive ileostomy and three patients revisional surgery. The FCSEMS were kept in place for a mean period of 34 (range: 6–65) days. Major complications occurred in 12 out of 29 patients (41.4%) and consisted of stent migration. Minor complications included two cases of transient fever, eight cases of abdominal or rectal pain, and one case of tenesmus. Conclusion: FCSEMS are considered a possible therapeutic option for treatment of postsurgical strictures and leaks. However, their efficacy in guaranteeing long-term anastomotic patency and leak closure is moderate. A major complication is migration. The use of FCSEMS for colonic postsurgical pathologies should be carefully evaluated for each patient.